2021
DOI: 10.2147/dddt.s341223
|View full text |Cite
|
Sign up to set email alerts
|

Saroglitazar – A Potential Therapeutic Option in Treating NASH? [Letter]

Abstract: We read the extremely informative study "Non-Alcoholic Steatohepatitis (NASH) -A Review of a Crowded Clinical Landscape, Driven by a Complex Disease" published by Fraile et al 1 in the prestigious journal "Drug Design, Development and Therapy". We would like to appreciate the remarkable work done by the authors on this thorough review, congratulate them on its successful publication, and make further contributions.This review discussed the potential mono-therapeutic options for Non-alcoholic steatohepatitis (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…9 In India, saroglitazar magnesium (Lipaglyn), approved for the treatment of T2D and dyslipidemia, has shown promising results in clinical trials evaluating its therapeutic role in NASH. 10 Saroglitazar is a non-thiazolidinedione and non-fibric acid derivative that acts as a dual regulator of lipid and glucose metabolism by activating PPARα/γ. It has insulin-sensitizing effects by activating PPARγ, which results in a reduction in blood glucose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In India, saroglitazar magnesium (Lipaglyn), approved for the treatment of T2D and dyslipidemia, has shown promising results in clinical trials evaluating its therapeutic role in NASH. 10 Saroglitazar is a non-thiazolidinedione and non-fibric acid derivative that acts as a dual regulator of lipid and glucose metabolism by activating PPARα/γ. It has insulin-sensitizing effects by activating PPARγ, which results in a reduction in blood glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In India, saroglitazar magnesium (Lipaglyn), approved for the treatment of T2D and dyslipidemia, has shown promising results in clinical trials evaluating its therapeutic role in NASH. 10…”
Section: Introductionmentioning
confidence: 99%
“…India approved saroglitazar in 2020 for the treatment of type-2 diabetes mellitus and NASH ( Sarkar et al, 2021 ). However, a phase 2 trial conducted in the United States indicated that the role of saroglitazar in a particular subset of patients with elevated alanine aminotransferase without histological endpoints cannot be recommended ( Kumar, Kulkarni & Jagdish, 2021 ; Shuja, Eqbal & Rehman, 2021 ). Therefore, there is an urgent need to develop pharmacological strategies for the treatment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%